2012
DOI: 10.1137/110821330
|View full text |Cite
|
Sign up to set email alerts
|

dqds with Aggressive Early Deflation

Abstract: Abstract. The dqds algorithm computes all the singular values of an n-by-n bidiagonal matrix to high relative accuracy in O(n 2 ) cost. Its efficient implementation is now available as a LAPACK subroutine and is the preferred algorithm for this purpose. In this paper we incorporate into dqds a technique called aggressive early deflation, which has been applied successfully to the Hessenberg QR algorithm. Extensive numerical experiments show that aggressive early deflation often reduces the dqds runtime signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…Alternatively, in [Dhillon 1997] it is suggested that, if eigenvalues are computed first, a "perfect shift" can be incorporated in the QR algorithm that causes deflation after only one iteration, though the same document uncovers certain challenges associated with this approach. -"Aggressive early deflation" has been developed to accelerate the QR algorithm for upper Hessenberg matrices [Braman et al 2001b], and the authors of [Nakatsukasa et al 2012] have extended the approach to the dqds algorithm. Thus, it may be possible to incorporate this technique into our restructured QR algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, in [Dhillon 1997] it is suggested that, if eigenvalues are computed first, a "perfect shift" can be incorporated in the QR algorithm that causes deflation after only one iteration, though the same document uncovers certain challenges associated with this approach. -"Aggressive early deflation" has been developed to accelerate the QR algorithm for upper Hessenberg matrices [Braman et al 2001b], and the authors of [Nakatsukasa et al 2012] have extended the approach to the dqds algorithm. Thus, it may be possible to incorporate this technique into our restructured QR algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Option B. The procedure invoked in the aggressive early deflation algorithm, see [12], is useful here. In our implementation we use this option since we found it usually saves some floating point operations over Option A.…”
Section: 1mentioning
confidence: 99%
“…To be more specific, let ψ = √ x. The bulge moves upward by one position by applying a Givens transformation from the right [12]:…”
Section: 1mentioning
confidence: 99%
See 2 more Smart Citations